2019
DOI: 10.1080/03007995.2019.1610370
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmia detection outcomes among patients monitored with the Zio patch system: a systematic literature review

Abstract: Objective: Cardiac arrhythmias can be serious and life threatening, and can impose a significant burden on healthcare systems. Recent technological advances in ambulatory electrocardiogram recorders have led to the development of unobtrusive wearable biosensors which allow physicians to study patients' continuous cardiac rhythm data collected over multiple weeks. The objective of this systematic literature review was to summarize evidence on the clinical effectiveness of the Zio 1 patch, a long-term, continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 39 publications
(80 reference statements)
1
26
0
1
Order By: Relevance
“…The study results showed a high rate (77.1%) of supraventricular tachycardia (SVT) detection among the patient population. Although this rate may seem higher as compared to the pooled data from 22 other studies (60.9%) (32), the results of a comparable study (35) indicate that patients with stroke and TIA may have a higher rate of SVT as compared to patients with no history of cerebral ischemia. A recent study of patients with pacemakers or implantable cardioverter-defibrillators showed subclinical atrial tachyarrhythmia preceding the development of clinical AF (36).…”
Section: Detection Rate Of Other Arrhythmiasmentioning
confidence: 58%
“…The study results showed a high rate (77.1%) of supraventricular tachycardia (SVT) detection among the patient population. Although this rate may seem higher as compared to the pooled data from 22 other studies (60.9%) (32), the results of a comparable study (35) indicate that patients with stroke and TIA may have a higher rate of SVT as compared to patients with no history of cerebral ischemia. A recent study of patients with pacemakers or implantable cardioverter-defibrillators showed subclinical atrial tachyarrhythmia preceding the development of clinical AF (36).…”
Section: Detection Rate Of Other Arrhythmiasmentioning
confidence: 58%
“…None of these measures say anything about whether episodes are clustered or distributed evenly during the monitored period, despite the fact that such information can be relevant for risk assessment of thrombus formation and ischemic stroke, as well as for better understanding arrhythmia progression. Since noninvasive, continuous monitoring has evolved to such a degree that a 14-day period or longer can be covered [35], the prerequisites for episode pattern analysis are becoming increasingly more favorable.…”
Section: Discussionmentioning
confidence: 99%
“…ZIO® Patch (iRhythm Technologies, Inc., San Francisco, CA, USA), a single-lead patch type device providing continuous ECG monitoring demonstrated higher rates of arrhythmia detection compared to conventional Holter monitor in several studies. 5 18 19 Its water-proof design and small device size without any electric lead or wire enable prolonged ECG monitoring of patients without bothering their daily activities. Another device named SEEQ® MCT (Medtronic, Inc., Minnesota, USA and Ireland, EU) provides wireless data transfer and real-time analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 These new devices have several advantages including light, small and water-proof design, efficient energy use and longer duration of monitoring, wireless data transfer, and no interruption of daily life over conventional Holter recorders. 5 These newer devices can improve quality of life of patients and elongate ECG monitoring duration, diagnostic accuracy and safety should be evaluated.…”
Section: Introductionmentioning
confidence: 99%